The Effect of Integrated Problem-Based Learning SDG Point 6 on Improving Sustainability Literacy of High School Students - Indriyani Amalia; Sariwulan Diana; Riandi Riandi (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine the effect of Problem-Based Learning (PBL) integrated with SDG point 6 on students’ sustainability literacy related to water pollution. A quasi-experimental method with a non-equivalent control group pretest–posttest design was employed involving two tenth-grade classes at a senior high school in Garut, selected through convenience sampling. The research instrument consisted of 15 essay questions measuring three aspects of sustainability literacy: knowledge, skills, and mindset. The instrument was validated by experts and demonstrated high reliability (Cronbach’s α = 0.92). Data were analyzed through normality and homogeneity tests followed by an Independent Samples T-test. The results indicated that there was no statistically significant difference in total post-test scores between the experimental class using SDG-integrated PBL and the control class using discovery learning (two-tailed Sig. = 0.07). However, the experimental class showed greater mean improvements, particularly in the skills and mindset aspects, compared to the control class. In conclusion, PBL integrated with SDG 6 shows a tendency to enhance students’ sustainability literacy, especially in terms of skills and mindset, although its overall effect was not statistically significant. The findings imply the need for better alignment between assessment instruments and learning contexts, student habituation to PBL, longer intervention periods, and further analyses to more sensitively evaluate instructional effectiveness.